2018
DOI: 10.1186/s13006-018-0156-y
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding practices and determinants of exclusive breastfeeding in a cross-sectional study at a child welfare clinic in Tema Manhean, Ghana

Abstract: BackgroundExclusive breastfeeding is important for child health and growth, but its practice is low in many developing countries. This study aimed at determining the breastfeeding practices and examining the sociodemographic characteristics that influence exclusive breastfeeding among mothers attending child welfare clinic at Manhean, in the Tema East Sub-Meteropolitan area of Greater Accra region of Ghana.MethodsThis was a cross-sectional study that employed a structured questionnaire to collect data among 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
64
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 33 publications
16
64
8
Order By: Relevance
“…In the Indian study, only 36.25% of mothers gave exclusive breastfeeding until six months [13], compared to 41% of mothers in Guatemala, these results being lower than the present study which found 51.5%; Higher data were found in advanced studies in Cali, Colombia 66.7% [19], Ghana 66% [20], Girón, Colombia 72% [17]. However, these studies do not reach the goal proposed by the WHO of 85% [11], which makes manifest the need to increase interdisciplinary efforts to reduce the deficiency.…”
Section: Practicescontrasting
confidence: 79%
“…In the Indian study, only 36.25% of mothers gave exclusive breastfeeding until six months [13], compared to 41% of mothers in Guatemala, these results being lower than the present study which found 51.5%; Higher data were found in advanced studies in Cali, Colombia 66.7% [19], Ghana 66% [20], Girón, Colombia 72% [17]. However, these studies do not reach the goal proposed by the WHO of 85% [11], which makes manifest the need to increase interdisciplinary efforts to reduce the deficiency.…”
Section: Practicescontrasting
confidence: 79%
“…9 Moreover an improved rates of exclusive breast feeding were also observed when expecting women were provided with awareness regarding the benefit of breast feeding in the form of antenatal breast feeding counseling which is not commonly practiced in our region. 11 Our results were validated by previous researches which stated that socio demographic factors such as nature of job, 10 younger age, 12 ethnicity, 12 family system, 13 working hours, 14 inter pregnancy interval, 15 number of children, 15 and family income 16 were significantly associated with exclusive breast feeding among working women.…”
Section: Discussionsupporting
confidence: 75%
“…17 as it was observed that experience in better child feeding practices come with increasing age. 12 Another significant factor found in our result was ethnicity. The influence of ethnicity on exclusive breast feeding could be explained by effect of different cultural beliefs and practices held by various ethnic groups on child health and breastfeeding rates.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Breastfeeding mothers need to be informed about strategies to prevent problems; at the same time, they need support in order to overcome problems they may face. Health care providers have been identi ed by mothers as the primary source of information on breastfeeding (12,13). Thus, the former could support mothers in preventing breastfeeding problems or managing them if they occurred.…”
Section: Introductionmentioning
confidence: 99%